2021
DOI: 10.1002/fsn3.2482
|View full text |Cite
|
Sign up to set email alerts
|

ω3PUFAs improve hepatic steatosis in postnatal overfed rats and HepG2 cells by inhibiting acetyl‐CoA carboxylase

Abstract: With the increasing prevalence of obese children, nonalcoholic fatty liver disease (NAFLD) has become one of the most common chronic liver diseases in pediatric population (Flisiak-Jackiewicz & Lebensztejn, 2019;Hales et al., 2017). The overall prevalence of pediatric NAFLD is approximately 10%, including up to 17% in teenagers and 40%-70% among obese children (Clemente et al., 2016).The onset of pediatric NAFLD is often asymptomatic, and hepatic lipid accumulation in the early period of NAFLD could more easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…SREBP-1c is a major regulator of fatty acid synthesis in the liver. It can regulate enzymes or proteins related to fatty acid synthesis such as ACC [ 37 ]. In the HFD group, the mRNA expression levels of SREBP-1c and ACC in the livers of mice were remarkably increased, while the mRNA expression levels of SREBP-1c and ACC were substantially decreased by B. lactis SF ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…SREBP-1c is a major regulator of fatty acid synthesis in the liver. It can regulate enzymes or proteins related to fatty acid synthesis such as ACC [ 37 ]. In the HFD group, the mRNA expression levels of SREBP-1c and ACC in the livers of mice were remarkably increased, while the mRNA expression levels of SREBP-1c and ACC were substantially decreased by B. lactis SF ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a cross‐sectional study, nut consumption was associated with a lower risk of NAFLD (calculated by FLI) in older adults (Tan et al, 2021 ). In another study, it was reported that an omega‐3 PUFA‐rich diet (fish oil diet) reduced the risk of NAFLD by inhibiting acetyl‐CoA carboxylase and sterol regulatory element‐binding protein‐1c (SREBP‐1c) (Zhou et al, 2021 ). Khan and Jackson ( 2018 ) found a significant relationship between pro‐inflammatory omega‐6 FAs intake and FBS, triglyceride, and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…One animal model designed to study the impact of childhood obesity was obtained by reducing the litter size from normal (eight to ten rat pups) to small (three to four offspring per dam) during the lactation period. This enables the offspring rat to suckle a higher quantity of milk when raised in a small litter (SL) compared with a normal litter (NL), resulting in a greater body weight gain [ 6 , 7 , 8 ] that is exacerbated after weaning when the animals receive high-density energy diets [ 9 ]. The overnutrition, overweight, and rapid growth that are produced in the infant rat under these conditions have a great influence on the health and metabolism of the adult animal [ 10 , 11 ], producing an increase in the prevalence of obesity, type 2 diabetes, metabolic syndrome, dyslipidemia, hypertension, and NAFLD developing in adulthood.…”
Section: Introductionmentioning
confidence: 99%